C-reactive protein in cardiovascular disease: clinical associations, conformation-dependent biology, and therapeutic perspectives - Bingxing Gong; Haiqin Xu; Honglan Liu; Mengmeng Wang; Kailin Yang; Junpeng Chen; Xiaoyang Guo; Tianqing Zhang; Liangqing Ge (Frontiers in Immunology, 2026)
C-reactive protein (CRP) is a widely used biomarker of systemic inflammation and cardiovascular risk. Its clinical and experimental relevance has been investigated across major cardiovascular disease (CVD) phenotypes, including coronary artery disease, heart failure, arrhythmias, cardiomyopathies, hypertension, and aortic aneurysm. High-sensitivity CRP (hs-CRP) assays detect low-grade systemic inflammation, and elevated circulating hs-CRP is associated with incident cardiovascular events, recurrent events, and mortality. CRP also exhibits conformation-dependent biological properties. Circulating pentameric CRP (pCRP) can undergo transition through modified pentameric CRP (pCRP*) to monomeric CRP (mCRP) at activated or damaged membranes. Experimental studies indicate that pCRP* and mCRP may exert localized effects on endothelial cells, vascular smooth muscle cells, immune cells, complement activation, coagulation, and extracellular matrix remodeling. However, observational, genetic, animal, and interventional evidence does not establish circulating CRP as a major independent cause of CVD, and the causal and clinical significance of tissue-associated CRP conformations remains unresolved. Clinically, hs-CRP- and CRP-based composite indices may support risk stratification and assessment of residual inflammatory risk, although their performance and thresholds vary across populations and clinical settings. Upstream anti-inflammatory and metabolic therapies can lower circulating CRP indirectly, whereas CRP apheresis, anti-CRP antibodies, and inhibitors of conformational transition are direct CRP-directed approaches that remain investigational. This review synthesizes clinical, structural, mechanistic, and therapeutic evidence for CRP across major CVD phenotypes and identifies priorities for conformation-specific measurement, causal evaluation, and target-specific intervention. At present, hs-CRP is principally a biomarker of inflammatory risk, whereas the therapeutic value of directly targeting CRP remains to be established.